Impact of Youtube Kids Impressions on Early Childhood Prosocial Behavior - Dewi, Sinta Kurnia; Deliana, Sri Maryati; Haryadi, Haryadi (Universitas Negeri Semarang, 2019)
The purpose of this study are (1) to analyze the influence of social media on early childhood prosocial behavior, (2) to investigate the influence of the number of Youtube kids social media display frequency on early childhood prosocial behavior, (3) to know the effect of the duration of Youtube kids social media shows on early childhood prosocial behavior, and (4) to analyze the influence of attention on Youtube kids social media shows that are watched on early childhood prosocial behavior. The research method uses a quantitative approach with non-experimental design and the data analyzed is as ex post facto dependent variable. The study population were 60 parents of students. The sampling technique in this study uses total sampling techniques or census techniques so that the number of samples were 60 parents. Data analysis used regression analysis. Based on the results of the study, the youtube kids give a positive impact on childhood prosocial behavior. The positive impact of youtube kids, in frequency, duration and attention aspect is discussed.